Support of a motivatsionno-target component of technology of formation of culture of brainwork of students on the basis of the resource approach - Ibragim Y.S (Kharkov National Pedagogical University, 2010)
Technology of providing of forming of motivational having a special purpose component of the rich in content judicial stage of forming of culture of mental work of students is developed. 157 students took part in an experiment. During development technology took into account resource approach. He consisted of systematic stimulation of different aspects of motivational sphere of personality. Technology of forming of motivational having a special purpose component of the rich in content judicial stage is grounded in theory. It provided positive changes in the motivational sphere of students.